PPELATIHAN PENGELOLAAN LIMBAH PLASTIK MENJADI KERAJINAN TANGAN GUNA MENINGKATKAN KREATIFITAS ANAK-ANAK - Agci Hikmawati; Haritsyah Haritsyah; Muhammad Yunan Prabowo; Al-Badrul Hafiz; Desi Sapitri; Sindy Martari; Murni Nofiri; Widayanti Widayanti; Rhesdea Wulan Dari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2020)
The aim of the program is to provide training in the use of plastic waste and to improve the effectiveness of children in ketapang in managing plastic waste into attractive, useful and valuable crafts. This training was conducted in Tanjung Ketapang village on 18 to 19 Febuarai 2020. In this training there were 10 participants and 11 students. This method of training used the technique (1) of socialization for material delivery to the participants, (2) The implementation of plastic waste management practices into flower pot-shaped handicrafts, (3) reflections made to evaluate the activities. The result of this community devotion is handicraft in the form of flower pots from used plastic material. This training enhances the creativity of children from works that have an artistic value that has a variety of motives.Â